2020
DOI: 10.1016/j.sjbs.2020.08.041
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of hysterosalpingographic findings among patients presenting with infertility

Abstract: Background Infertility is a global health issue and hysterosalpingography (HSG) is a valuable radiological tool in infertility workup and remains a main modality for investigating female infertility. However, the HSG findings of infertility are not the same worldwide. This study aimed at evaluating the incidence of HSG findings in patients investigated for primary and secondary infertility, correlating these findings with their clinical data that reflect the infertility causes and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
9
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 33 publications
8
9
2
Order By: Relevance
“…Although some studies have reported primary infertility as the predominant type among women who had HSG for evaluation of infertility [ 7 , 19 ], secondary infertility was the most predominant type of infertility in this study. Similar studies in in Nigeria [ 4 , 14 , 15 ] and other parts of the world [ 19 ] have reported secondary infertility as the commonest type among female partners of couples with infertility undergoing HSG. This finding may be attributed to the prevalent cause of female infertility in the study population such as pelvic infection or pelvic inflammatory disease.…”
Section: Discussioncontrasting
confidence: 52%
“…Although some studies have reported primary infertility as the predominant type among women who had HSG for evaluation of infertility [ 7 , 19 ], secondary infertility was the most predominant type of infertility in this study. Similar studies in in Nigeria [ 4 , 14 , 15 ] and other parts of the world [ 19 ] have reported secondary infertility as the commonest type among female partners of couples with infertility undergoing HSG. This finding may be attributed to the prevalent cause of female infertility in the study population such as pelvic infection or pelvic inflammatory disease.…”
Section: Discussioncontrasting
confidence: 52%
“…The age ranges in women undergoing HSG on account of secondary infertility is scarce in the available literature. However, our finding was in agreement with 30-39 years recorded in a study of women with infertility done in Ile-Ife 7 in a society of predominantly different ethnic and cultural group from ours, but of the similar racial and religious disposition; but differed from 26-36 years age group recorded by Toufig et al 32 in a different country with different cultural, religious and educational background. This suggests a cultural, religious and educational influence.…”
Section: Discussionsupporting
confidence: 93%
“…Among women with infertility, strong association was found between tubal blockage and past medical history suggestive of previous PID by Toufig et al 32 and this is in concordance with that obtained in Ile-Ife. 7 But, the report of a strong association between tubal abnormalities and history of previous abdominopelvic surgery by Toufig et al 32 is at variance with the report by a study in Benin 27 that found no correlations between tubal blockage and history of previous pelvic surgery. The finding of significant association between tubal blockage and positive history of previous D&C by a study in Ile-Ife 7 also differs from the report of no significant correlation between the two variables by another in Benin.…”
Section: Intrauterine Adhesions Peritubal Adhesions and Tubal Occlusi...supporting
confidence: 86%
See 1 more Smart Citation
“…It is easily accessible and is typically the initial step in the imaging evaluation of the fallopian tubes in cases of infertility, particularly in underdeveloped nations like our own. 10 The results of this study indicate that the average age is 32.50 years, and it also demonstrated that the majority of infertile women who presented themselves for HSG were between the ages of 30 and 34 years old. This should not come as a surprise given that we have reached the pinnacle of the female reproduction stage.…”
Section: Discussionmentioning
confidence: 58%